2018
DOI: 10.1155/2018/5764187
|View full text |Cite
|
Sign up to set email alerts
|

Control ofCryptococcus GattiiBiofilms by an Ethanolic Extract ofCochlospermum Regium(Schrank) Pilger Leaves

Abstract: Cryptococcus gattii is an etiologic agent of cryptococcosis and a serious disease that affects immunocompromised and immunocompetent patients worldwide. The therapeutic arsenal used to treat cryptococcosis is limited to a few antifungal agents, and the ability of C. gattii to form biofilms may hinder treatment and decrease its susceptibility to antifungal agents. The objective of this study was to evaluate the antifungal and antibiofilm activities of an ethanolic extract of Cochlospermum regium (Schrank) Pilge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In traditional medicine C regium xylopodium, is used to cure gastric problems, ulcers, rheumatism, vaginal discharge, prostatic infections, abscesses, in analgesia, anti-hypertensive, antiinflammatory, in the treatment of arthritis and acne (Carvalho et al, 2018) . Studies evaluating the phytomedicinal properties for xylopodium and leaves showed important biological activities explored mainly from hydroethanolic, hydromethanolic, ethanolic, methanolic extracts and their fractions, as an antimicrobial agent on Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, Candida tropicalis and Cryptococcus gattii (Leme et al, 2017;Carvalho et al, 2018;Almeida-Apolonio et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In traditional medicine C regium xylopodium, is used to cure gastric problems, ulcers, rheumatism, vaginal discharge, prostatic infections, abscesses, in analgesia, anti-hypertensive, antiinflammatory, in the treatment of arthritis and acne (Carvalho et al, 2018) . Studies evaluating the phytomedicinal properties for xylopodium and leaves showed important biological activities explored mainly from hydroethanolic, hydromethanolic, ethanolic, methanolic extracts and their fractions, as an antimicrobial agent on Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, Candida tropicalis and Cryptococcus gattii (Leme et al, 2017;Carvalho et al, 2018;Almeida-Apolonio et al, 2018).…”
Section: Introductionmentioning
confidence: 99%